Addition Rice Husk on the Density and Impact Strength of Non-Asbestos Brake Pad Composites Prepared by The Hand Layup Method - Fitriyana, Deni Fajar; Doni Widodo, Rahmat; Kriswanto, Kriswanto; Athoillah, Ahmad; Prasetyo, Ares Yudi; Alrasyid, Mochamad Dzaki; Aripin, Muhammad Bustanul; Dimyati, Saeful; Irawan, Agustinus Purna; Cionita, Tezara; Siregar, Januar Parlaungan; Ismail, Rifky; et al. (Lembaga Penelitian dan Pengabdian Universitas Negeri Semarang, 2022)
In train operation, brakes are an essential component because they involve the safety of passengers. Therefore, brake pads must be replaced periodically according to their lifespan. Currently, the most widely used train brake pad material is composite. Unfortunately, most train brake pads in Indonesia still use imported products because no industry can produce train brake pads of the desired quality. This study aims to manufacture and characterize composite materials for friction material for train brake pads that meet quality standards to substitute imported products. It needs to reduce dependence on imported products while at the same time encouraging the strengthening of the structure of the domestic manufacturing industry. In addition, agricultural waste in rice husks will be used to produce more environmentally friendly products. In this study, the composition of the types of composite materials, which include binder, reinforcement, abrasive, and filler materials, will be examined. Making composite materials in this study will use the hand layup method. Material characterization carried out includes impact testing and density. The characterization results show that using rice husk as a filler greatly influences the density of the resulting composite material. Specimen 5, made from epoxy, rice husk, iron filings, and Al2O3 (wt.%) at 50%, 20%, 15%, and 15%, respectively, was able to produce a higher density compared to the composite without rice husk and epoxy material. The results of this density test support the results of the impact tests that have been carried out. The higher the rice husk content, the higher the density produced. Adding rice husk can increase the mechanical properties of the resulting composite material.